A mosaic mutation in the CLCNKB gene causing Bartter syndrome: A case report - Zhou, Lan; Chen, Xiaohui; Xiong, Jiaojiao; Lei, Ling (Frontiers in Pediatrics, 2023)
Background Type III Bartter syndrome (BS) is an autosomal recessive disease caused by mutations in the CLCNKB (chloride voltage-gated channel Kb) gene that encodes CLC-Kb. CLC-Kb is mainly located in the thick ascending limb of Henle's loop and regulates chloride efﬂux from tubular epithelial cells to the interstitium. Type III BS is characterized by metabolic alkalosis, renal salt wasting, hyperreninemia, and hyperaldosteronism with normal blood pressure. Case presentation We reported the case of a 3-day-old girl whose initial symptom we diagnosed as jaundice, but we accidentally found metabolic alkalosis. She showed recurrent metabolic alkalosis, hypokalemia, and hypochloremia and also had hyperreninemia and hyperaldosteronism with normal blood pressure. Both oral potassium supplements and potassium infusion therapy were unable to entirely restore the electrolyte imbalance. She was suspected of Bartter syndrome and genetic tests were performed on her and her parents. Next-generation sequencing identified CLCNKB gene mutation including heterozygous mutation c.1257delC (p.M421Cfs*58) and a low-level mutation c.595G > T (p.E199*); both mutations were also verified in the parents. Conclusion We reported the case of a classic Bartter syndrome in a newborn with a heterozygous frameshift mutation and a mosaic non-sense mutation in the CLCNKB gene.